Processing of waste polyethylene into polymer-ceramic composite through lipid assisted melt compounding - Bensah, Y.D.; Agyei-Tuffour, B.; Damoah, L.N.W.; Efavi, J.K. (ARPN Journal of Engineering and Applied Sciences, 2012)
In this work, a modified approach to melt compounding has been successfully developed to study the dispersion of kaolin particles in polyethylene and properties of polyethylene-kaolin clay composites. The process involved the use of melt compounding technique with vegetable lipid acting as a melting medium with the capability to enhance miscibility of the polyethylene with the kaolin which is necessary for strength improvement of the polyethylene-kaolin composite. Eight different compositional batches were formulated and cast at 245 °C. In all the thermal and mechanical properties as well the microstructure of the composites were studied. Comparisons of the composites with pristine polyethylene-lipid have shown an improved glass transition temperature (Tg) and the thermal decomposition temperatures as a result of changes in the chemical structure. Proportional kaolin additions did not change the crystallization temperature (Tc) of the blends as compared to the pristine polyethylene-lipid blend. Incorporation of 60% kaolin by weight in the polyethylene-lipid matrix significantly improved the mechanical properties of the composites to its peak and an increased compressive strength of 2.0 to 8.7 MPa has been measured. Scanning electron microscopic (SEM) analyses shows the formation of a web-like entanglement caused by the dispersion of the kaolin particles in the matrix. © 2006-2012 Asian Research Publishing Network (ARPN).
Keywords: Coconut oil; Kaolin; Lipid; Melt compounding; Polymer ceramic composite; Waste polyethylene